2021
DOI: 10.5254/rct.21.79994
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Water-Swellable Compounds Based on Nitrile Rubber With Varied Acrylonitrile Content

Abstract: This article examines the development of water-swellable rubbers for oil and gas production packer equipment. The object of the investigation is to document the effect of rubber's acrylonitrile content on the swelling of the elastomers modified with sodium-carboxymethyl cellulose and a copolymer of acrylamide and potassium acrylate. After testing the samples at room temperature, the most influential factor in a material's swelling was discovered to be the mineral content in the liquids imitating well fluids. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The obtained product was filtered in a vacuum filter, and then dried in air. As a polymer base for creating sleeves for swelling packers, oil-and gasoline-resistant thermostable nitrile butadiene rubber (NBR) is widely used [42][43][44]; synthetic isoprene rubber, methyl-styrene-butadiene rubber, ethylene propylene rubber and their mixtures are used to a lesser extent [45][46][47]. In this work, nitrile butadiene rubber grade BNKS-28 AMN was used.…”
Section: Carboxylation Of Cellulosementioning
confidence: 99%
“…The obtained product was filtered in a vacuum filter, and then dried in air. As a polymer base for creating sleeves for swelling packers, oil-and gasoline-resistant thermostable nitrile butadiene rubber (NBR) is widely used [42][43][44]; synthetic isoprene rubber, methyl-styrene-butadiene rubber, ethylene propylene rubber and their mixtures are used to a lesser extent [45][46][47]. In this work, nitrile butadiene rubber grade BNKS-28 AMN was used.…”
Section: Carboxylation Of Cellulosementioning
confidence: 99%
“…[1,2,17] Generally, elastomers do not swell in water irrespective of their polarities. Vaniev et al [27] carried a study on the water swelling behaviors of NBR, it was observed that the polar moieties (acrylonitrile content) of NBR did not have any serious influence on it water-swelling properties. Thus, water swelling of elastomers can only be achieved through careful engineering.…”
Section: Introductionmentioning
confidence: 99%